Food Preferences and Foraging Activity of Asian Weaver Ants, Oecophylla smaragdina (Fabricius) (Hymenoptera: Formicidae) - Marcela Pimid; Abu Hassan Ahmad; Kumara Thevan Krishnan; Joanna Scian (Tropical Life Sciences Research, 2019)
Weaver ant (Oecophylla smaragdina) is an important insect community in tree canopies, but little is known about their foraging behaviours. Therefore, a field experiment was conducted in order to assess the food preferences and foraging activity of weaver ants for three consecutive days. The food preferences of the weaver ants were evaluated using three types of foods (tuna, chicken skin, and milk powder) containing varying contents of protein, lipid, and carbohydrate. The foraging activity was examined based on two parameters, namely temperature and relative humidity which were recorded throughout the study. Results revealed that food higher in protein content was highly preferred by the O. smaragdina compared to foods with lipid and carbohydrate contents, and the foraging activity of the O. smaragdina was significantly influenced by both temperature and relative humidity. The present study exhibits how the weaver ants respond to different types of foods and indirectly, forming a strategic foraging activity to maximise their food supplies for their colony. Kerengga (Oecophylla smaragdina) adalah satu komuniti serangga yang penting di kanopi pokok. Walau bagaimanapun, kajian tentang aktiviti pencarian makanan kerengga adalah terhad. Oleh sebab itu, satu kajian lapangan dijalankan untuk mengkaji pemilihan makanan dan aktiviti pencarian makanan oleh semut ini dijalankan selama tiga hari. Pemilihan makanan oleh kerengga ini dikaji dengan menggunakan tiga jenis makanan (tuna, kulit ayam, dan susu tepung) yang mengandungi protein, lipid, dan karbohidrat. Aktiviti pencarian makanan dikaji berdasarkan dua parameter iaitu suhu persekitaran dan kelembapan relatif yang direkod sepanjang tempoh experimen. Keputusan experimen menunjukkan O. smaragdina lebih menggemari makanan berprotein berbanding makanan berlipid dan berkabohidrat, serta aktiviti pencarian makanan dipengaruhi oleh suhu persekitaran dan kelembapan relatif. Hasil kajian ini menunjukkan bagaimana kerengga bertindak balas terhadap tiga jenis makanan yang berbeza dan secara tidak langsung, menunjukkan aktiviti pencarian makanan yang strategik untuk memaksimumkan bekalan makanan kepada koloni mereka.